2015
DOI: 10.1111/xen.12173
|View full text |Cite
|
Sign up to set email alerts
|

Human thrombomodulin regulates complement activation as well as the coagulation cascade in xeno‐immune response

Abstract: Background: With the introduction of the a1, 3-galactosyltransferase gene-knockout (GT-KO) pig and its pivotal role in preventing hyperacute rejection (HAR), coagulation remains a considerable obstacle yet to be overcome in order to provide long-term xenograft survival. Thrombomodulin (TBM) plays a critical anticoagulant and anti-inflammatory role in its part of the protein C pathway. Many studies have demonstrated the strong anticoagulant effects of TBM in xenotransplantation, but its complement regulatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(61 reference statements)
2
19
1
Order By: Relevance
“…Only in combination with GTKO and hCD46, activation of coagulation was inhibited as both complement and endothelial cell activation were reduced (Figs ). The interference of hTBM with thrombin generation is in line with the data from other studies . In regard to the aspects of anti‐inflammatory and complement regulatory properties and in contrast to other studies , we found no protective effect of the mono‐transgenic PAEC expressing hTBM.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Only in combination with GTKO and hCD46, activation of coagulation was inhibited as both complement and endothelial cell activation were reduced (Figs ). The interference of hTBM with thrombin generation is in line with the data from other studies . In regard to the aspects of anti‐inflammatory and complement regulatory properties and in contrast to other studies , we found no protective effect of the mono‐transgenic PAEC expressing hTBM.…”
Section: Discussionsupporting
confidence: 90%
“…The interference of hTBM with thrombin generation is in line with the data from other studies . In regard to the aspects of anti‐inflammatory and complement regulatory properties and in contrast to other studies , we found no protective effect of the mono‐transgenic PAEC expressing hTBM. The complement regulatory effect of hTBM observed in other studies was described as based on thrombin inhibition, since thrombin can activate the complement system via cleavage of C3 and C5 to C3a and C5a .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…TM is structurally divided into five domains (i.e., N-terminal lectin-like domain, epidermal growth factor (EGF)-like repeats domain, serine-threonine rich domain, transmembrane domain, and cytoplasmic tail), each of which has unique functional properties [3]. Studies by various groups have shown that TM alone or the TM-thrombin complex suppress inflammation, coagulation, oxidative stress, complement activation, sepsis, adhesion of immune cells to the endothelium, and radiation damage [4,5,6,7,8]. Moreover, the TM-thrombin complex transforms protein C to activated protein C (APC), which is known to have anti-inflammatory, anti-coagulant, and cytoprotective properties [4].…”
Section: Introductionmentioning
confidence: 99%